Two genes in a pathogenicity gene cluster encoding secreted proteins are required for appressorial penetration and infection of the maize anthracnose fungus Colletotrichum graminicola. (21st October 2019) - Eisermann, Iris; Weihmann, Fabian; Krijger, Jorrit‐Jan; Kröling, Christian; Hause, Gerd; Menzel, Matthias; Pienkny, Silke; Kiesow, Andreas; Deising, Holger B.; Wirsel, Stefan G. R.
Summary: To avoid pathogen‐associated molecular pattern recognition, the hemibiotrophic maize pathogen Colletotrichum graminicola secretes proteins mediating the establishment of biotrophy. Targeted deletion of 26 individual candidate genes and seven gene clusters comprising 32 genes of C . graminicola identified a pathogenicity cluster ( CLU5 ) of five co‐linear genes, all of which, with the exception of CLU5b, encode secreted proteins. Targeted deletion of all genes of CLU5 revealed that CLU5a and CLU5d are required for full appressorial penetration competence, with virulence deficiencies independent of the host genotype and organ inoculated. Cytorrhysis experiments and microscopy showed that Δ clu5a mutants form pressurized appressoria, but they are hampered in forming penetration pores and fail to differentiate a penetration peg. Whereas Δ clu5d mutants elicited WT‐like papillae, albeit at increased frequencies, papillae induced by Δ clu5a mutants were much smaller than those elicited by the WT. Synteny of CLU 5 is not only conserved in Colletotrichum spp. but also in additional species of Sordariomycetes including insect pathogens and saprophytes suggesting importance of CLU 5 for fungal biology. Since CLU5a and CLU5d also occur in non‐pathogenic fungi and since they are expressed prior to plant invasion and even in vegetative hyphae, the encoded proteins probably do not act primarily as effectors.